Atemporal equilibria: pro- and retroactive coding in the dynamics of cognitive microstructures - Elliott, Mark A. (Frontiers in Psychology, 2014)
Detection reaction times to a grouping target are expedited when the target is preceded by repeated presentation of a priming stimulus presented below detection thresholds in a premask matrix presented at specific frequencies between 27-68 Hz. Frequency-specific priming can be explained as a function of the return phase of the priming stimulus relative to premask matrix frequency, indicating one consequence of repeating stimulation is pre-activation of a prime. By varying the frequency and phase of priming-stimulus relative to target presentation it is also shown that given an interaction in phase between the target presentations relative to the return phase of the prime, target coding is expedited by a prime that achieves maximum activation at a phase that would precede priming-stimulus presentation by several tens of milliseconds. However, this cognitive response is flexible enough to be able to achieve an identical prime retroactively, that is, at a phase during or subsequent to priming-stimulus presentation. This occurs if there is no interaction between the phase of target presentation and priming-stimulus presentation. On this basis, it can be concluded that by virtue of the relationship between stimulus events and the dynamics of microstructural cognition, cognition may exist in a temporal context that can shift from past to future states. Consequently and at this low level of psychological function, the conventional, one-dimensional model of time flow - from future to past states does not fully explain cognitive function. Instead, depending upon the interaction in phase between different coding frequencies, the same form of cognition can anticipate or retroactively code events. In so far as our cognition provides a content structure for consciousness, our psychological lives may be based upon an ability to travel backwards and forwards across very short intervals of time.